Synthesis and characterization of fe-al alloy with different sintering temperature - Maimum Razali
The aim of this final year project is to study the effect of the sintering temperature on the intermetallics properties. Beside it is to find the best sintering temperature for Fe-Al alloy system and to investigate physical and mechanical properties of the intermetallics produced. It is also to improve the alloys properties.